2012
DOI: 10.4314/ejesm.v5i4.s22
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Symptoms and Viruses Associated with Cowpea (<em>Vigna Unguiculata</em> (L).) in the Agroecological Zones of Kwara State, Nigeria

Abstract: A comprehensive field survey was carried out in 2011 spanning thirty locations within the forest and savannah agroecologies of Kwara State, Nigeria. This was with the objective of having an overview of the prevalence of virus disease symptoms and to specifically identify the viruses infecting cowpea (Vigna unguiculata .L.) in Kwara State. Data were collected on the prevalence of some peculiar virus symptoms on cowpea plants on growing on farms in each location. Symptomatic cowpea leaves were also collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 3 publications
5
16
0
Order By: Relevance
“…Symptoms observed in the field (mosaic, leaf mottling, vein clearing and necrotic lesion) were similar to symptoms reported elsewhere on legumes affected by viral diseases (Akinjogunla, 2005;Aliyu et al, 2012). The varying symptoms observed in the study are suggestive of different viruses which infect cowpeas in the study area (Aliyu et al, 2012).…”
Section: The Virus Symptoms Observed On Cowpea On the Fieldsupporting
confidence: 87%
See 2 more Smart Citations
“…Symptoms observed in the field (mosaic, leaf mottling, vein clearing and necrotic lesion) were similar to symptoms reported elsewhere on legumes affected by viral diseases (Akinjogunla, 2005;Aliyu et al, 2012). The varying symptoms observed in the study are suggestive of different viruses which infect cowpeas in the study area (Aliyu et al, 2012).…”
Section: The Virus Symptoms Observed On Cowpea On the Fieldsupporting
confidence: 87%
“…Symptoms observed in the field (mosaic, leaf mottling, vein clearing and necrotic lesion) were similar to symptoms reported elsewhere on legumes affected by viral diseases (Akinjogunla, 2005;Aliyu et al, 2012). The varying symptoms observed in the study are suggestive of different viruses which infect cowpeas in the study area (Aliyu et al, 2012). The variation in symptoms observed in the study could be attributed to the type of viral strains infecting the cowpea, cowpea cultivar, the time of infection, light intensity, environmental temperature, and mixed infections (Jones et al, 1991;Aliyu et al, 2012).…”
Section: The Virus Symptoms Observed On Cowpea On the Fieldsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been reported that symptom expression depends on the virus type or strain, genotype, species and plant age, time of the year and environmental conditions and some viruses cause similar or related symptoms (Shoyinka et al, 1997). Some symptoms such as mosaic, necrosis, chlorosis, vein banding, stunted growth, leaf deformation, and mottling are associated with viruses such as Cowpea aphid borne mosaic virus (CABMV), Blackeye cowpea mosaic virus (BICMV), Cowpea yellow mosaic virus (CYMV) (Aliyu et al, 2012;Orawu, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Surveys conducted in Kwara State, Nigeria by Aliyu et al (2012), indicated the presence of viruses in mixed infections on cowpea in the agroecological zones of the State.…”
Section: Cowpea Vigna Unguiculata L (Walp) Is One Of the Major Fomentioning
confidence: 99%